The utilization of infra-zygomatic crest (izc) bone screw in non-extraction treatment of class II malocclusion: A Case Report - Andriani, Vina; Paskalin, Zenith; Laviana, Avi; Evangelina, Ida Ayu; Mardiati, Endah; Sayuti, Elih (Padjadjaran Journal of Dentistry, 2025)
Introduction: Temporary Anchorage Devices (TADs), absolute anchorage systems with minimal side effects on orthodontic mechanical movements, can be alternatives to wider non-surgical, non-extraction, and non-compliance treatments. The placement of extra-radicular mini-screws at the infra zygomatic crest (IZC) is one of the most commonly used approaches for skeletal anchorage. Maxillary arch distalization with IZC can be effectively performed in Class II malocclusion patients with large overjet using non-extraction treatment, especially due to increasing patient demands to avoid extractions. The aim of this case report is to demonstrate the effectiveness of infrazygomatic crest (IZC) extra-radicular TADs for maxillary distalization in a Class II malocclusion cases treated without extractions. Case report: A 16-year-old female patient came to the Orthodontic Clinic with the complaint of forward upper teeth, Class II Angle malocclusion and Class I skeletal with a convex facial profile, deep overbite, overjet 6 mm, posterior scissor bite, diastema between teeth 32-33, and deep curve of Spee. The patient was treated with non-extraction fixed orthodontics using a self-ligating system prescription, utilizing extra radicular Temporary Anchorage Devices (TADs) at the infra zygomatic crest measuring 2 x 12 mm for maxillary retraction. Following the maxillary retraction treatment, successful outcomes were achieved as the overjet decreased from 6 mm to 3 mm; Class I molar and canine relationships were established; and the distance from I to NA was reduced from 11 mm to 5 mm. Conclusion: The clinical use of infra-zygomatic crest (IZC) bone screw in non-extraction treatment of Class II malocclusion case was successfully conducted with non-extraction fixed orthodontic treatment.